Justification of the Thematic Legislation in Indonesia: Justifikasi Pembentukan Undang-Undang Tematik di Indonesia - Rauta, Umbu; Kurnia, Titon Slamet; Sousa, Freidelino Paixao Ramos Alves de; Soares, Adérito de Jesus; Kishan, Marcelino Ceasar; Jeconiah, Bernadeta Adriana Sandra (Jurnal Konstitusi, 2025)
The use of the omnibus method has been controversial since the enactment of the Job Creation Law due to its cross-sectoral nature, making the resulting legislation difficult for the public to understand. The validity of laws created using the omnibus method does not only depend on the validity of the omnibus method because it has been recognized by law. The paper aims to critique the Omnibus method of Article 64 (1) letter b of the Law on Legislation Making and its application resulting in the Job Creation Law, Law No. 6 of 2023 which is not thematic so it is not easy for the public to understand. The novelty of this article is the idea that the implementation of the omnibus method must also be accompanied by the resulting laws being thematic so that they can be easily understood. Thus we propose the thematic omnibus method. The thematic principle in omnibus method is born from the dictates of the Rule of Law principle, which is regulated in the principle of clarity of purpose and the principle of clarity of formulation, which is a form of the necessity of intelligibility in legislation.